Porcine circovirus 2 and 3 in wild boars in Southern Brazil - Santo,Ana Carolina Dal (2022)
ABSTRACT: Porcine circovirus 2 (PCV2) has a considerable economic impact on the pork industry worldwide for more than two decades. In 2016, a new circovirus, porcine circovirus 3 (PCV3), was described; since then, it has been reported to be associated with diseased or even in clinically healthy swine in several countries. Considering the importance of wild boars as reservoirs of swine pathogens and the extensive distribution of these animals in Rio Grande do Sul and throughout the national territory, we searched for PCV2 and PCV3 in twenty-six wild boars coupled with necropsy and histologic examination of the sampled animals. Using PCR, 182 tissue samples were analyzed, including the heart, kidneys, liver, lung, lymph nodes, spleen, and tonsils. PCV2 and PCV3 were detected in 57.7% (15/26) and 15.4% (4/26) of wild boars, respectively. Furthermore, co-infection with PCV2 and PCV3 was detected in one of these animals, with PCV2 or PCV3 DNA detection in multiple organs. Histological examination showed mild to moderate and multifocal lymphoplasmacytic interstitial nephritis distributed randomly throughout the renal cortex, apparently unrelated to PCV2 or PCV3 detection. The wild boar population in Brazil is extensive, indicating the presence of a larger number of swine pathogen hosts. In the present study, more than half of the wild boars harbored PCV2; and although less frequently, PCV3 was also detected. Therefore, free-living wild boars can serve as reservoirs of swine circoviruses in southern Brazil.